Diet and Body Composition of Soccer (Football) Players and Referees in Iran. Issue 4 (July 2021) - Jibril, Aliyu Tijani; Beba, Mohammad; Shab-Bidar, Sakineh; Seifbarghi, Tohid; Djafarian, Kurosh
Abstract : We evaluated the associations of micronutrient adequacy (measured by the mean adequacy ratio of intakes to nutrient recommendations) and dietary acid load with body composition in 218 football (soccer) players and referees in Iran to provide insights that might help to optimize nutrition and overall performance. Despite the alkaline nature of their diets, there was no association between dietary acid load indices and body composition, and the mean adequacy ratio was positively associated only with percentage body fat ( β = .17, P = .01). Further studies with larger sample sizes and longer durations are recommended.